Morbidity associated with sickle cell trait carriers - Seck, Moussa; Soubaiga, Yannick; Faye, Blaise Félix; Sy, Diariétou; Touré, Sokhna Aissatou; Dieng, Nata; Sall, Abibatou; Touré, Awa Oumar; Diop, Saliou (International Journal of Research in Medical Sciences, 2016)
Background: Sickle cell trait carriers has long considered asymptomatic. This affirmation is now challenged because many patients complain of osteoarticular pain and several organic degenerative complications in particular; renal, eye and sudden death have been described. The objective of this study was to evaluate the morbidity of sickle cell trait and identify risk factors associated. Methods: This is a prospective study with duration of 16 months including 50 patients with sickle cell trait received regular visits (every 6 months) for painful events. Biological assessment was carried out systematically to eliminate rheumatic disease (CRP, ASLO, latex Waler Rose) or metabolic disorders (serum calcium, serum magnesium, and serum uric acid). A correlation between clinical and laboratory data was performed to study the relationship between morbidity observed and biological abnormalities. Results: Mean age of patients was 32 years (12-59) and mean age at diagnosis was 24 years (12-55 years). Sex ratio M/F was 0.16. Clinical symptoms were osteoarticular pain (88%), headache (86%), abdominal pain (76%), muscle cramps (70%), dizziness (56%), biliary lithiasis (6%), femoral head osteonecrosis (2%) and gross haematuria (2%). Seventeen patients (34%) had abnormal metabolic or rheumatic analysis. No risk factor associated with morbidity of patients was identified. Conclusions: This work has allowed us to find that the symptoms presented by sickle cell trait patients are dominated by painful events. This morbidity associated with porting sickle cell trait was not secondary to inflammatory or metabolic disorders or physical activity.